PENGARUH PERSEPSI DAN MOTIVASI TERHADAP MINAT MAHASISWA JURUSAN AKUNTANSI BERKARIR DI BIDANG PERPAJAKAN (Studi Empiris pada Mahasiswa Akuntansi Universitas Islam Malang) - Miftakhul Ayu Anggraeni; Maslichah Maslichah; Dwiyani Sudaryanti (Universitas Islam Malang, 2020)
The purpose of this study was to determine the effect of perception and motivation on the interests of students majoring in career accounting in taxation. The population in this study were students of the Accounting Study Program Faculty of Economics and Business Malang Islamic University class of 2016. The sample was selected using purposive sampling and obtained 171 students based on criteria. This study uses multiple linear regression models. The results of this study indicate that perception and motivation influence the interests of the career in taxation. Perception has a positive effect on career interests in the field of taxation. Motivation has a positive effect on career interests in the field.Keywords: Perception, Motivation, and Career Interest